Evaluation of viability and survival of free and maltodextrin microencapsulated Bifidobacterium animalis subsp. animalis through spray-drying process - Corpas-Iguarán, Eduardo Javid; Triviño-Valencia, Jessica; Tapasco-Alzate, Omar; Garcés-Gómez, Yeison Alberto (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
Bifidobacterium animalis subsp. animalis is a microorganism integrated into the human intestinal microbiota and performs a probiotic function through mechanisms that promote the absorption of nutrients, the modulation of the immune system, and the production of lactic acid, among other aspects. Microencapsulation using maltodextrin promotes the protection of microorganisms against physical and chemical factors, improving viability over time. Bifidobacterium animalis subsp. animalis was microencapsulated through spray-drying using maltodextrin. Survival under pH conditions, bile salts, and temperature were evaluated as well as its viability during storage conditions. The viability of the encapsulated agent stored at 25 °C remained high and constant during the first three weeks. The results for free and microencapsulated thermal tolerance showed an important difference among survival percentages of each tested temperature, and microencapsulation showed a protective effect against temperatures like or lower than 55 °C. Regarding pH 2.5 exposure for 3h, there is a survival of 5.38% for free microorganisms in contrast to 11.87% for encapsulated, whereas in a pH 3.5 for 3h, the encapsulated agent showed a survival of 23%. The results obtained from encapsulated cells stressed with a 1g/L concentration of bile salts showed a survival of 19%, while free cells presented a total loss of viability when subjected for 3h at the same concentration. Microencapsulated Bifidobacterium animalis subsp. animalis demonstrated potential for its use incorporated into foods, but it is necessary to improve viability conditions during storage and survival under gastric stress conditions.